Comparative Analysis of Gene Expressed in Trunking and Non-Trunking Metroxylon sagu Leaves Utilizing Transcriptome Sequencing - Wei Jie, Yan (Unimas Institutional Repository, 2023)
Sago palm (Metroxylon sagu) is an important agricultural starch-producing palm that contributes to Malaysia’s economics, especially in the State of Sarawak. In this palm tree, storage-starch is located in the trunk of the plant. Under normal conditions, the sago palm develops its trunk after 4 - 5 years of being planted. However, sago palm planted on deep-peat soil failed to develop their trunk even after 17 years of being planted. This phenomenon is known as ‘non-trunking’, which eliminates the economic value of the palms. Numerous research has been done to address the phenomenon, but the molecular mechanisms of sago palm responding toward the responsible stresses are still lacking. Therefore, this study used the transcriptomic approach to determine differentially expressed enzymes and pathways causing the non-trunking phenomenon. A newly improved CTAB extraction protocol was used for RNA extraction, followed by next-generation transcriptome sequencing using the BGISEQ-500 platform. The sequence was de novo-assembled using TRINITY software package and the differentially expressed genes (DEGs) were identified using DESeq2 algorithm. A total of 40.11 Gb were sequenced from the sago palm leaf samples. The assembled sequence produced 102,447 Unigenes, with an N50 score of 1,809 bp and a GC ratio of 44.34%. The alignment of Unigenes with seven functional databases (NR, NT, GO, KOG, KEGG, SwissProt and InterPro) resulted in the annotation of 65,523 (63.96%) genes. A total of 936 DEGs were identified. Analysis of the DEG data and the pathways involved showed that the non-trunking phenomenon in sago palm is caused by the nutrient deficiency of nitrogen, phosphate and sulphate. The DEG analysis also indicated that nutrient starvation negatively affects the normal biological processes in the sago palm; aggravating the effect of boron and aluminium toxicity; and the malnourished sago palm is also more susceptible to pathogenic infection; which ultimately leads to stunted growth and development of the plant.